2020
DOI: 10.1177/0731948720906490
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Text Structure Instruction Supports Expository Text Comprehension for Adolescents With Learning Disabilities: A Systematic Review

Abstract: This systematic review article summarizes the effects of explicit text structure instruction on expository text comprehension for adolescents with learning disabilities or at risk for reading failure. A thorough literature search with four databases and backward citation search identified nine studies published in the past 22 years for inclusion in the review. The findings revealed medium to large effect sizes on expository reading comprehension outcome measures, providing moderately strong evidence in support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…While the findings are preliminary, they are promising given the gains obtained in text structure awareness and comprehension via a relatively short-term intervention. Previous reviews of text structure instruction have reported large effect sizes for compare–contrast comprehension interventions, indicating that clinically significant increases in text comprehension are possible through explicit text structure instruction (Hall-Mills & Marante, 2020; Hebert et al, 2016; Pyle et al, 2017). The strong effects we noted via visual analysis (e.g., PND) and quantitative analysis (e.g., Tau- U ) for the current participants compare favorably with findings from other text structure interventions.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…While the findings are preliminary, they are promising given the gains obtained in text structure awareness and comprehension via a relatively short-term intervention. Previous reviews of text structure instruction have reported large effect sizes for compare–contrast comprehension interventions, indicating that clinically significant increases in text comprehension are possible through explicit text structure instruction (Hall-Mills & Marante, 2020; Hebert et al, 2016; Pyle et al, 2017). The strong effects we noted via visual analysis (e.g., PND) and quantitative analysis (e.g., Tau- U ) for the current participants compare favorably with findings from other text structure interventions.…”
Section: Discussionmentioning
confidence: 98%
“…However, adolescents may not yet have complete knowledge of expository text structures (Williams et al, 2014). Common expository text structures include description (provides information for an event or topic), problem–solution (describes how to solve a problem), cause–effect (describes a causal relationship), sequencing (provides a series of steps in order of occurrence), and compare–contrast (describes similarities and differences between concepts) (Hall-Mills & Marante, 2020).…”
Section: Importance Of Text Structure In Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explicit instruction is a teaching model that demonstrates to students what to do and how to do it. Historically, explicit instruction is employed with younger children (Kruit et al, 2018), with students learning to write and speak languages (Graham et al, 2013) or with students who live with learning disabilities (Hall-Mills & Marante, 2020). Interestingly, van de Kamp et al (2015) conducted a small scale study with 147 secondary school students in visual arts education and found that explicit instruction was very useful to reinforce metacognitive divergent higher-order thinking skills and knowledge, while direct instruction impeded originality and creativity.…”
Section: Explicit Instruction As a Teaching Toolmentioning
confidence: 99%